GRP78 Nanobody‐Directed Immunotoxin Activates Innate Immunity Through STING Pathway to Synergize Tumor Immunotherapy - Huifang Wang; Runhua Zhou; Chengchao Xu; Lingyun Dai; Rui Hou; Liuhai Zheng; Chunjin Fu; Guangwei Shi; Jingwei Wang; Yang Li; Jinpeng Cen; Xiaolong Xu; et al. (Advanced Science)
Abstract The lack of targetable antigens poses a significant challenge in developing effective cancer‐targeted therapies. Cell surface translocation of endoplasmic reticulum (ER) chaperones, such as glucose‐regulated protein 78 (GRP78), during malignancy, drug resistance, and ER stress induced by therapies, offers a promising pan‐cancer target. To target GRP78, nanobody C5, identified from a phage library and exhibiting high affinity for human and mouse GRP78, is utilized to develop the Pseudomonas exotoxin (PE) immunotoxin C5‐PE38. C5‐PE38 induced ER stress, apoptosis and immunogenic cell death in targeted cells and showed antitumor efficacy against colorectal cancer and melanoma models without obvious toxicity. Mechanistically, transcriptome profiling showed that C5‐PE38 reshaped the tumor immune microenvironment with enhanced innate and adaptive immune response and response to interferon beta. Moreover, C5‐PE38‐induced cell death could trans‐activate STING pathway in dendritic cells and macrophages, promoting CD8+ T cell infiltration. It also sensitizes both primary and metastatic melanomas to anti‐PD1 therapy, partly through STING activation. Overall, this study unveils a feasible GRP78 nanobody‐directed therapy strategy for single or combinatorial cancer intervention. This work finds that C5‐PE38‐induced cell death stimulates STING‐dependent cytosolic DNA release to promote antitumor immunity, a mechanism not previously reported for PE38, providing valuable insights for its clinical use.